Bulked Segregant RNA Sequencing Revealed Difference Between Virulent and Avirulent Brown Planthoppers - Guan, Wei; Shan, Junhan; Gao, Mingyang; Guo, Jianping; Wu, Di; Zhang, Qian; Wang, Jing; Chen, Rongzhi; Du, Bo; Zhu, Lili; He, Guangcun (Frontiers in Plant Science, 2022)
The brown planthopper (Nilaparvata lugens Stål, BPH) is one of the most devastating insect pests of rice (Oryza sativa L.). It has been demonstrated that the BPH exists as a complex of populations that are virulent or avirulent to rice varieties with different genes for resistance. This study performed bulked segregant RNA sequencing (BSR-seq) to identify differentially expressed genes (DEGs) and genetic loci associated with the virulence of BPH to resistant rice plant. BPH insects that are highly virulent or avirulent to rice plants carrying resistance gene Bph15 were selected from an F2 population to form two contrasting bulks. BSR-seq identified 751 DEGs between two bulks. The avirulent insects up-regulated carbohydrate metabolism, amino acid metabolism, nucleotide metabolism, endocrine system, and signal transduction in response to Bph15 resistance. Lipid metabolism and digestive system pathways were crucial for the virulent BPHs to adapt the resistant rice YHY15. We identified 47 SNPs in 33 genes linked with BPH virulence. The possible roles of the candidate genes in BPH virulence were discussed. Our results provide necessary information for studying the virulence mechanism of BPH and developing control strategies.